2021
DOI: 10.2298/vsp181202050d
|View full text |Cite
|
Sign up to set email alerts
|

Dental health status in children with type 1 diabetes mellitus in Montenegro

Abstract: Background/Aim. The number of children with diabetes is constantly increasing. The aim of this study was to evaluate oral health in children with type 1 diabetes mellitus compared to healthy children. Methods. The study included 177 patients aged 10-15 years, divided into two groups. Group T1DM, made up of children with type I diabetes mellitus. Control group was healthy children. The dental health was assessed using the DMFT index. The Plaque Index (PI) according to Silness-Löe and the Calculus Index (CI) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 22 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…All in all, the included articles were from 14 countries. There were five studies from India [ 35 39 ], four from Iran [ 27 , 40 – 42 ],two from Saudi Arabia [ 43 , 44 ], two from Egypt [ 45 , 46 ], two from Greece [ 47 , 48 ], one from Kuwait [ 14 ], one from The United States [ 49 ] one from Poland [ 50 ], one from Portugal [ 51 ], one from Montenegro [ 52 ], one from Kosovo [ 53 ], one from Turkey [ 54 ], one from Brazil [ 55 ], one from Iraq [ 56 ], one from Libya [ 57 ], one from Sweden [ 58 ], one from Belgium [ 29 ], one from Romania [ 59 ], one from Italy [ 60 ], one from Hong Kong [ 61 ], one from Finland [ 62 ], one from Lithuania [ 63 ] and one from Hungary [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All in all, the included articles were from 14 countries. There were five studies from India [ 35 39 ], four from Iran [ 27 , 40 – 42 ],two from Saudi Arabia [ 43 , 44 ], two from Egypt [ 45 , 46 ], two from Greece [ 47 , 48 ], one from Kuwait [ 14 ], one from The United States [ 49 ] one from Poland [ 50 ], one from Portugal [ 51 ], one from Montenegro [ 52 ], one from Kosovo [ 53 ], one from Turkey [ 54 ], one from Brazil [ 55 ], one from Iraq [ 56 ], one from Libya [ 57 ], one from Sweden [ 58 ], one from Belgium [ 29 ], one from Romania [ 59 ], one from Italy [ 60 ], one from Hong Kong [ 61 ], one from Finland [ 62 ], one from Lithuania [ 63 ] and one from Hungary [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies did not find statistically significant differences between the study group and the control group [ 27 , 29 , 38 , 41 44 , 46 – 52 , 54 , 55 , 57 , 59 62 , 64 ]. There were six studies revealing higher DMFT values in the DM groups [ 14 , 35 , 40 , 45 , 53 , 56 ]; and five studies found that children living with type 1 DM had lower DMFT values, which means a better caries prevalence [ 36 , 37 , 39 , 58 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations